Penerapan Teknologi Dalam Rangka Mendukung Percepatan Pemulihan Ekonomi di Desa Sindangmekar - Mulyana, Subhan; Fauzie, Arief Arrahman; Putri, Tania Adzani; Azis, Muhamad Andhika Abdul; Nurholis, Tiara Dwi Putri; Munggaran, Syahrul Azwar; Ramadhan, Dekha; Kurniawan, Muhammad Wilham; Fauziah, Syifa; Lestari, Fina Ayu; Hawari, Ciptaraka Nurhisam; Nurazizah, Siti Ulfah; Dewi, Tiara; Natsir, Dimas Muhammad Fauzy; Firdaus, Muhammad Naufal; Wijaya, Ari Sukma; Tajudin, Ridwan; Budiman, Budiman; Almunawar, M Rifki; Yusuf, David (Institut Teknologi Garut, 2023)
Real Work Lecture (KKN) is a form of community service activity by students with a cross-scientific and sectoral approach at certain times and regions in Indonesia. The implementation of KKN activities lasts between one month and takes place in an area at the village level of Sindangmekar. The method used is a field survey method, outreach about workshops, especially in the utilization of natural resources into products that have high selling power and as business opportunities for the community and understanding of digital literacy. The aim is to increase skills and knowledge regarding the use of digital devices that are good and right, so that people can develop smart, creative and productive attitudes which are an option in the learning that has been carried out. When the activity is carried out, all involved are required to comply with the health protocol. The result of this activity is that people can apply knowledge when needed.